PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS PENDIDIKAN KABUPATEN/KOTA - Maddatuang, Maddatuang (Parameter, 2015)
Employees' performance is affected by some factors, such as, attitude of human resources, work management and mechanism, and facilities. This research is aimed at obtaining valid and reliable information related to the effect of leadership style, organizational culture, and work motivation on employees' performance or Regency/Municipal Offices of National Education in South Sulawesi Province. 135 respondents were chosen randomly using the formula of Cohen to be the samples of the study. The data were collected by survey technique and analyzed by path analysis. The data analysis and interpretation indicated that employees' performance is affected directly by leadership style, organizational culture, and work motivation. The findings lead to the conclusion that any changes occurred at the employees it could be affected by leadership style, organizational culture, and work motivation. It implies that leadership style, organizational culture, and work motivation should be improved in order to have better performance of employees of Regency/Municipal Offices of National Education in South Sulawesi Province besides other additional variabels.